Transportation scheme for the disabled in London and Kuala Lumpur / Azmu Syuhaida Ayob … [et al.] - Ayob, Azmu Syuhaida; Shahrudin, Nurazatul Farhana; Berahim, Nurul Athiyah Hanim; Hassan, Zakeah (2009)
This research paper is basically about the comparison of laws enforcement on the rights of the disabled in related to Malaysia's public service vehicles, especially on buses. In order to determine the extent of the laws in Malaysia that protect the disabled public access, this research paper had made the comparison with the laws in United Kingdom, London. The reason behind the comparison with United Kingdom is because it is well known that London is the city that implemented one of the most effective laws that protects the disabled rights in terms of public transport in the world. Through the research that had been done in this project paper, it was found out that the laws in Malaysia which currently governing the rights of public transportation on the disabled is not properly and thoroughly drafted if compared to United Kingdom's. Thus, a few recommendations had been proposed in order to improve the laws as to strengthen the disabled rights to a proper convenience access towards public transportations as they also had the same equal rights with the normal people.